Sunrays in a chilly winter - Nolutshungu, Simphiwe (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2015)
In both my English and IsiXhosa poetry, my themes are love, politics, and the social issues of rural communities, and include my own life experiences, both good and bad. My poems are mainly short narrative accounts of township life. Although they do have a broad educational purpose, they do not preach to the reader. In IsiXhosa, my poetic forms are influenced by the works of J J R Jolobe, W N Mbovane, P T Mtuze, and my English poems by Pablo Neruda, Mafika Pascal Gwala, Garcia Lorca and others.,Intliziyo yona izimele gxebe ifihlakele Iyimfihlo, kumagumbi omphefumlo. Iyafunxa, ifukame kulo magumbi amxinwa. Iingcango, mba! Zivaliwe! Maxa wambi zide zixel' isisila senkukhu, sona sibonwa mhla ligquthayo. Vul' amehlo ubaz' iindlebe uchul' ukunyathela. Yiza ndikubambe ngesandla, sivul' iingcango! Masivul' iingcango zentliziyo yam, sikrobe ngaphakathi! Masithi ntla" ntla kumagumb' amathathu kuphela! Masithi ntla" ntla, kwelepolitiki yakwaXhosa, Kaloku nam ndingumXhosa! Masithi ntla" ntla kwelifukame, i.z.i.x.i.n.g.a.x.i n.o.b.u.n.c.w.a.n.e. b.o.t.h.a.n.d.o, kaloku nam ndinemithamb' ebalek' igaz' eliqhumayo! Ucango lokugqibela lukungenisa kwigumbi elinezidl' umzi, Kaloku nam ndizalwa kulo mzi wakwaXhoooooosa!Â  Â ,This thesis is presented in two parts: English and isiXhosa.
Iincgango zentliziyo
Keywords: Creative writing (Higher education) -- South Africa; South African poetry (English) -- Study and teaching (Higher); South African poetry (English) -- 21st century; South Africa -- Poetry